Corporate Governance Objectives of Labor Union Shareholders: Evidence from Proxy Voting - Agrawal, Ashwini K. (Review of Financial Studies, 2012)
Labor union pension funds have become increasingly vocal in governance matters; however, their motives are subject to fierce debate. I examine the proxy votes of AFL-CIO union funds around an exogenous change in the union representation of workers across firms. AFL-CIO affiliated shareholders become significantly less opposed to directors once the AFL-CIO labor organization no longer represents a firm's workers. Other institutional investors, including mutual funds and public pension funds, do not exhibit similar voting behavior. Union opposition is also associated with negative valuation effects. The data suggest that some investors pursue worker interests, rather than maximize shareholder value alone.